Optimizing the Hydrodynamic Performance of Unmanned Sailboats by Adjusting the Structure of the Keel and Rudder - Zongrui Hao; Kailin Li; Gang Liu; Shixuan Liu (Journal of Marine Science and Engineering)
The hydrodynamic performance optimization of unmanned sailboats is of great significance for achieving long-endurance, long-distance, and highly concealed navigation. Based on the existing design of unmanned sailboats, this study optimized the keel and rudder, proposed specific optimization strategies, and evaluated and determined the optimal structural scheme. Subsequently, a comprehensive analysis of the resistance performance, stability, and maneuverability of the unmanned sailboat before and after optimization was conducted using CFD numerical simulations and MAXSURF software. The results show that the optimized keel effectively reduces the contact area with water, significantly lowering the overall resistance of the unmanned sailboat. In terms of stability, the optimized design greatly improves initial stability, thereby enhancing the overall stability of the unmanned sailboat. Regarding maneuverability, the optimized unmanned sailboat achieves maximum steering force at a rudder angle of 15°, demonstrating excellent maneuvering capabilities. Overall, the results indicate that the optimized unmanned sailboat exhibits outstanding hydrodynamic performance, providing reliable theoretical references and technical support for the design and optimization of unmanned sailboats.